2022
DOI: 10.38194/jurkom.v5i1.441
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Hotel Public Relations In Crisis Management During The Covid-19 Pandemic

Abstract: The hotel industry has felt the impact of the COVID-19 pandemic. The social restriction policy implemented by the government to prevent the transmission of the virus has made mobility levels decline, and hotel occupancy rates have drastically decreased. This pandemic has created severe crisis management. This research was conducted at two five-star hotels in Yogyakarta to determine how public relations practices deal with crisis management. One hotel is a local brand, and the other is included in an internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…The positive effect of communication and public relations as a marketing crisis management practice and hotel performance holds significant implications for the hotel industry in Mombasa County and Kenya. This alignment with previous research (Leta & Chan, 2021;Susilo & Prayudi, 2022) underscores effective communication's pivotal role in enhancing hotels' resilience and prosperity through marketing practices, especially in crises.…”
Section: Discussion Conclusion and Recommendations Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The positive effect of communication and public relations as a marketing crisis management practice and hotel performance holds significant implications for the hotel industry in Mombasa County and Kenya. This alignment with previous research (Leta & Chan, 2021;Susilo & Prayudi, 2022) underscores effective communication's pivotal role in enhancing hotels' resilience and prosperity through marketing practices, especially in crises.…”
Section: Discussion Conclusion and Recommendations Discussionsupporting
confidence: 79%
“…The study's findings suggest a connection between public relations and customer-related outcomes. Susilo and Prayudi (2022) delved into the role of hotel public relations in crisis management during the COVID-19 pandemic. They used qualitative research methods to explore how public relations practices were employed by two five-star hotels in Yogyakarta, Indonesia, to manage the crisis.…”
Section: Communication and Public Relations Strategies And Hotel Perf...mentioning
confidence: 99%
“…According to the findings of the research, it is advised that management should make an effort to combat significant challenges influencing crisis management and devise strategies that may enhance and safeguard organizational interests during a time of crisis. The aspect of crisis management and public relations has to be strengthened in media companies, and there is a need for the management to do so (Susilo & Prayudi, 2022). The findings of the study indicated that the concept of crisis management and public relations is one that must always be included in ongoing management concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Krisis yang dihadapi oleh Kemendikbud merupakan krisis yang menjadi dampak dari Covid-19. Kondisi Covid-19 menyebabkan krisis yang dialami cukup "spesial" karena krisis Covid-19 tidak memiliki tahap pra-krisis, yang umumnya digunakan sebagai tahapan untuk mempersiapkan mitigasi krisis (Susilo & Prayudi, 2022). Berdasarkan Situational Crisis Comunication Theroy, krisis yang disebabkan oleh bencana alam atau wabah penyakit dikategorikan sebagai victim crisis, dimana lembaga tidak memiliki keterlibatan atas terjadinya krisis, sehingga tuntutan publik bagi organisasi untuk melakukan krisis sangat kecil.…”
Section: Pendahuluanunclassified